Il bianco e il nero nella fraseologia italiana e spagnola - Stanič, Daša (Vestnik za tuje jezike, 2012)
This article considers the semantic values of "white" and "black" in Italian and Spanish phraseology. These two colors are among all those that form the greatest number of phraseological units. Consulting Italian and Spanish dictionaries, bilingual dictionaries, phraseological dictionaries and chosen corpora of the two languages, 232 phraseological units with "white" and "black" were found. The most common type are collocations of the type adjective plus noun. In this paper, the phraseological units are classified according to their semantic values. It has been discovered that while the semantic values of "white" can in both languages be positive (in the majority) and negative, the values of "black" are almost all negative. Variants of phraseological units that can be formed with both colours as well as examples of phraseological units containing both colours were highlighted. In most of these examples the "white" and "black" represent the opposite. Only a few phraseological units with "white" and "black" directly linked to the Italian and Spanish culture were found. They refer to mafia, football, fascism and bullfighting.
Keywords: Italian; italijanščina; Spanish; španščina; kontrastivna analiza; phraseology; frazeologija; barve